GABAergic cell types and modulation of GABAergic synaptic transmission by group III metabotropic glutamate receptors in the human neocortex - Lukacs, IP (2021)
The neocortex is a layered, modular structure on the surface of the mammalian brain, which together with other brain structures supports behavioural adaptation to the changing environment. It is greatly expanded in humans and is thought to be necessary for unique human behaviours such as abstraction and language, functions which contribute to the high flexibility of human behaviour and underlie the adaptability of the species.